Cartografia de uma intervenção comunitária para prevenção de DST/HIV/AIDS - Lucas, Márcia Cavalcante Vinhas (2013)
Community-based interventions have been presented as a proposal of operationalization of the concept of vulnerability to STD/Aids prevention. This study aimed to analyze the Community intervention developed through the project Strengthening of Community action networks for STD/Aids prevention: know and intervenein, at Mãe Luiza neighborhood, in the city of Natal, State of Rio Grande do Norte, Brazil. The study was conducted in the same location where intervention occurs and took as time reference the first 30 months of construction and deployment process, from April 2010 until December 2012. This is research with qualitative approach, participatory character, developed from the immersion of the researcher in the field, being this community intervention itself. In this perspective, the study approximates to the Cartographic method in which the researcher-researched is engendered in the acts and effects research. The data-generating sources were the memories of the researcher from the field notes, written narratives of subjects involved in the intervention and documents pertaining to the project. In the methodological path of cartography, the image of the rhizome by Deleuze and Guattari (1995) has accompanied the immersion in the field given the nature of research-intervention which approach to the concept of object-Rhizome. The presentation of results was composed for the attempted rhizomatic and a hypertext representation, based on the descriptive narrative taken from the documentary analysis and the multi-faceted narratives with the voices, the looks and the affections narrated by the subject involved, respectively. On the path taken, three lanes were drawn as synthesis of learning produced by experience-that can contribute to understanding the process under study, in his singular character, and reflections on other experiences of community intervention: track 1- Community intervention as active-reflective space and a cause; track 2 Inclusion as power and challenge of community involvement; track 3 Sustainability as A challenge of Community intervention. The study indicates that community intervention is presented as a potential producer of health as also produces practical and creative skills, subjects and inventive in the daily life of the community with a view to reinventing knowledge and practices for the prevention of STD/HIV/Aids